Les Mémoires de Madame Roland : être femme dans la tourmente de l’Histoire - Anne Coudreuse (Itinéraires)
Mme Roland’s Mémoires are a hybrid of public and private, of History and intimacy. She wrote them during her incarceration in 1793. They are divided into two very distinct parts: the strictly historical Memoirs on the one hand and, on the other hand, the “Mémoires particuliers,” which chronicle the private life of the Parisian bourgeoisie from 1760 to 1780. This article explores the implications of the author’s gender in “Mémoires historiques,” since the memoirist is a woman, and what is more, she is the wife of a minister, who was criticized for allowing himself to be influenced by her and she was subjected to very violent attacks by the enemies of Roland.